PROBLEMATIKA PENYIDIKAN KASUS NARKOTIKA DALAM UPAYA MEMUTUS JARINGAN PEREDARAN GELAP NARKOTIKA (Studi Kasus Penyidikan oleh Badan Narkotika Nasional Provinsi Daerah Istimewa Yogyakarta) - Widyaputra, Endra; Harjiyatni, Francisca Romana; Nurharyanto, Eko (Kajian Hasil Penelitian Hukum, 2023)
This study aims to identify the problems by National Narcotics Board investigators in an effort to break the illicit narcotics trafficking network. In addition, it also examines the efforts made by the National Narcotics Board to overcome the problem. This research is a normative legal research using a statute approach, case approach and conceptual approach by combining primary and secondary data. The data obtained from the study were analyzed descriptively qualitatively. The results showed several internal and external problems by BNN investigators in the investigation to break the network of narcotics cases, such as difficulties in evidence, rapid technological development, budget constraints, lack of human resources, complexity of narcotics networks, changes in the type and form of narcotics, suboptimal investigation techniques, corruption and collusion, resistance from related parties in the network, limitations in legal regulations, conflicts of interest, and lack of cooperation from other parties. In addition, this analysis also explains the efforts made by BNNP DIY to overcome the problems of the investigation. These efforts include optimizing investigations and collecting evidence, making maximum use of existing technology, proposing an increase in the budget, increasing the number of personnel, increasing the capacity of investigators, strengthening legal regulations, improving the supervision and accountability system, and increasing cooperation with other agencies